REDESIGN UI/UX PADA APLIKASI BCA MOBILE MENGGUNAKAN METODE LEAN UX - Winardi, Michelle; Muawwal, Ahyar; Renny (STMIK KHARISMA Makassar, 2024)
BCA Mobile is a mobile banking application from PT Bank Central Asia Tbk. which enables customers to perform various types of banking transactions digitally. UI/UX plays an important role in the success of an application because good design can create a positive user experience and increase user satisfaction using the application. The results of observations collected through the rating and review columns on the Play Store and App Store show several problems experienced by users related to the UI/UX of the BCA Mobile application, as well as the results of usability testing from distributing the system usability scale (SUS) questionnaire before redesign to 30 respondents getting a score of 55.85 with an